Psychotherapist-Patient Privilege, Recordkeeping, and Maintaining Psychotherapy Case Notes in Professional Practice: The Need for Ethical and Policy Reform - Mills, Jon (Canadian Journal of Counselling and Psychotherapy, 2014)
A growing trend in Canadian mental healthcare professes that the best standard of practice is to keep complete notes and correspondence of all patient transactions in the mental health practitioner’s file, including a record of intimate personal details revealed in therapy. This file, however, is subject to intrusive inspection by third parties who may ask to view its contents. This creates a conundrum and a potential risk for the field of mental health. Professionals of all kinds are asked to keep in confidence whatever is disclosed in sessions, but the law prohibits privileged communication. This article challenges the distinction between privilege and confidentiality, and discusses the recording and filing of psychotherapy case notes, as well as the greater ethical questions these issues generate. I advocate a corrective: an alternative method of recordkeeping that maintains files for process notes separate from the official clinical record. This procedure insulates the patient and therapist from potential risk of ethical and legal exploitation inherent in our current presumption that all clinical notes and records are subject to disclosure and inclusion in the client’s file. The future of professional policy is at stake for all mental health professionals in Canada unless this issue is addressed.